2008
DOI: 10.1007/s00424-008-0480-y
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of troponin C affinity for the thin filament by different cross-bridge states in skinned skeletal muscle fibers

Abstract: In vertebrate skeletal muscle, the C-domain of troponin C (TnC) serves as an anchor; the N-domain regulates the position of troponin-tropomyosin on the thin filament after changes in intracellular Ca2+. Another type of thin-filament regulation is provided by cross-bridges. In this study, we use skinned fibers reconstituted with chicken recombinant TnC (rTnC) to examine TnC-thin filament affinity when cross-bridges containing different ligands are formed. Dissociation and equilibrium binding of apo-TnC (i.e., l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
(79 reference statements)
0
5
1
Order By: Relevance
“…ATPase activation, in the presence of Ca 2ϩ , demonstrated that D145E, located in the C-terminal domain, displayed a significant increase in the ability to activate actomyosin ATPase. Recently it was shown that different types of cross-bridges can modulate TnC affinity for the thin filament demonstrating the influence of myosin on the C-terminal domain of TnC (43). Here the C-terminal domain HCM mutation D145E strengthens this concept as it shows the influence of this domain on actomyosin function.…”
Section: Discussionmentioning
confidence: 50%
“…ATPase activation, in the presence of Ca 2ϩ , demonstrated that D145E, located in the C-terminal domain, displayed a significant increase in the ability to activate actomyosin ATPase. Recently it was shown that different types of cross-bridges can modulate TnC affinity for the thin filament demonstrating the influence of myosin on the C-terminal domain of TnC (43). Here the C-terminal domain HCM mutation D145E strengthens this concept as it shows the influence of this domain on actomyosin function.…”
Section: Discussionmentioning
confidence: 50%
“…2, A and C), it is likely that Ca 2ϩ uptake rate could not be reduced (39). Thus, the reduced tension of Tg ϩ EDL was associated with a decreased cross bridge dissociation rate, which could be affected by either NO or ROS as shown in the literature (14,24,38,39). These results suggested that chronic production of TNF-␣ likely affected the cross bridge dissociation rate of Tg ϩ EDL under both PO 2 conditions, consistent with the hypothesis by Reid et al (31) that TNF-␣ negatively affected either myosin ATPase activity or the thin-filament Ca 2ϩ kinetics.…”
Section: Discussionmentioning
confidence: 86%
“…In comparison, the previously described HCM cTnC mutants A8V and D145E increased thin filament Ca 2ϩ affinity with (⌬pCa 50 s of ϩ0.14 and ϩ0.08), respectively (33). It is well known that the number of cross-bridges can modulate both Ca 2ϩ sensitivity and TnC affinity for the thin filament (41)(42)(43)(44)(45)(46)(47). Therefore, the addition of myosin S1 was used to assess whether strong cross-bridge formation indirectly (ϪATP) modulated the Ca 2ϩ affinity of the mutant containing thin and thick filament differently than the WT (41).…”
Section: Journal Of Biological Chemistry 31851mentioning
confidence: 89%